(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: The resultant effect of a gunshot injury is mostly severe bleeding which leads to hypovolemic shock;a condition that is characterized by inadequate delivery of oxygen to vital organs. Objective: Present study had focused on the prevalence of gunshot wounds, alsoclinical consequencesdepending on differences in anatomical sites, age, gender with management strategies accordingly. Materials and Methods: The study design is retrospective in nature with quantitative approach and the study reviewed the data in the registers beginning from January to December 2017. Demographic data of the patients, anatomical sites of injuries, and findings of clinical outcomes had been retrospectively evaluated. Results: 1145 patients having gunshot wounds (GSW)had been included in the study (M/F= 1067 (93%)/78 (7%)). Average incidence of head injuries had been found as 8,75% which had showed a peak rate during May with a percentage of 11%. Thoracic injuries which had an average incidence of 11,3% had the highest rates during May, January, February and June. Abdominal injuries had showed a steady decline beginning from January (24%) till June (20%) with having least percentage of injury during May (13%).Only 10% of healthcare workers were among educated first aiders who transported the patients. Meanwhile,the majority had consisted of non-educatedones who took the patients to the hospital at the largest proportion of the casualties which include families, friends and close relatives. Mortalities (n=87 (8%)) were attributed mostlyto abdominaln=18 (21%), thoracic n=16 (18%), lower limbn=16 (18%)) and head n=14 (16%) injuries withdecreasing frequency. Conclusions: Deaths due to gunshot wounds (GSW) had been reported highestamong young aged population who are between 21 and 40 years of age. Considering that only 10% of rescue teams were among educated health care givers, this actual rate of mortality given in the present study can be lowered much more if the state can provide more educated staff, and also more fundamental first-care educations could be given for the public as well. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.401-403